“Back to normalcy” and daily life of Ukrainian returnees after World War II - Dobrzhanskyi, Oleksandr; Strilchuk, Lyudmyla (Riga, Latvia: “Baltija Publishing”, 2023)
The proposed monograph presents some aspects of everyday life of the population of Western Ukraine in the first postwar years. In particular, the daily life of peasants, teachers, schoolchildren, Ukrainian insurgents and un- derground, displaced and deported persons, etc. Separate studies are devoted to the historiography of the problem. The research can be useful for scientists, teachers, students, pupils, and all who are interested in the history of Ukraine of the twentieth century.
Western Ukrainian lands in the first postwar years (1944–1953): everyday life: Collective Monograph
Keywords: Western Ukrainian lands; Ukrainian returnees; daily life; after World War II